The economics of monetary integration - Grauwe, Paul de (Oxford University Press, 1994)
This Revised Second Edition covers recent events in the EMS, including the collapse of the ERM; includes fully updated empirical evidence; includes discussion of new theoretical developments such as target zone models and credibility testing; and introduces the political issues surrounding the move to monetary union. This popular textbook on monetary integration has now been fully revised and updated with expanded chapters on recent important events in the EMS, new empirical evidence, and coverage of further theoretical developments. This lucid and authoritative view will remain an invaluable undergraduate textbook.